Dwa nieznane średniowieczne dokumenty do dziejów lwowskiego kościoła Św. Ducha - Trawka, Renata (Archiwa, Biblioteki i Muzea Kościelne, 2017)
In the W. Stefanyk Library of the National Academy of Sciences of Ukraine in Lviv, under the reference number: Fond 5, op. 1, spr. 2155, there is a 16th-century manuscript, which contains, among others, the copies of several documents of the 14th and 15th centuries. The documents were prepared on the initiative of Adam Mniszkowski, a provost of the Holy Spirit Hospital and a prebendary of St. Catherine’s Chapel at the Lviv Low Castle. Among them are two unpublished documents concerning the endowment of the Holy Spirit Church in Lviv. The first of them-produced by the Archbishop of Halicz Jakub Strepa in 1399- confirms that the nobleman Michał of Malechów gave the rector of the mentioned church an annual rent from the income of the inn in Malechów. The other document was prepared in 1405 by Jakub, a rector of the Holy Spirit Church in Lviv and a judicial vicar of Halicz. He gave Stanisław Żelko, a village leader assistant, the meadow in Sroki together with the forest and the oak tree area with the aim of making it arable land in exchange for the annual rent paid to each rector of the hospital church after the period of wolnizna (the period during which a settler was exempt from paying duties). An analysis of the form indicates that this latter document was also produced in the office of the Archbishop of Halicz. The list of the witnesses to the document includes representatives of the nobility of Lviv and Przemyśl and the townspeople of Lviv. In addition to the characteristics of the content of the both documents, the article also presents their critical editing.